Functional improvement of natural Saccharomyces cerevisiae yeast strains by cell surface molecular engineering - Sara Granuzzo; Monica Rossetto; Lucio Zennaro; Francesca Righetto; Paolo Antoniali; Raffaele Lopreiato (Biology Direct)
Abstract Background Cellular boundaries of microorganisms can be modified by the expression in the cell wall of specific proteins endowed with relevant properties, improving their functional performance. So far, the surface display (SD) technique had been widely employed in the yeast Saccharomyces cerevisiae, but it was limited to few laboratory strains and never explored in sauvage strains, i.e., isolated from natural environment, which are featured by higher levels of genetic variability, leading to peculiar phenotypic traits of possible advantage in biotechnology. Results In this work, a series of plasmids performing SD in natural yeast strains have been generated and further characterized by multiple functional and biochemical assays, providing the first experimental evidence that natural strains of S.cerevisiae can be genetically modified to express on their cell wall a protein-of-interest, which retains its biological competence. Interestingly, data further demonstrated that engineered strains expressing (transiently or stably) metal-binding proteins or peptides on cell surface exhibit significantly enhanced metal adsorption properties. Conclusions The molecular tools presented here can be very useful for yeast research community, as the plasmids efficiently support the surface engineering in virtually all S.cerevisiae strains, independently from either genetic background, source, or applications (wine, beer, bread). Overall, data strongly suggest that, upon genetic modification, S. cerevisiae strains isolated from natural environments could serve as promising platforms for biotechnological applications, as heavy metals removal or enzymes immobilization. Importantly, the strains investigated here represent only a small fraction of the multitude of S. cerevisiae strains present in nature yet to be isolated.